UPAYA HUKUM BANDING SEBAGAI SARANA PERLINDUNGAN HAK PARA PIHAK DALAM PERKARA PERDATA - Edwin Yuliska (Ensiklopedia of Journal, 2026)
Appeal as a legal remedy constitutes one of the ordinary legal remedies within the civil justice system in Indonesia, granted to parties who feel aggrieved by a judgment rendered by a court of first instance. An appeal functions as a means to request a re-examination by the High Court of the decision of the District Court, both in terms of the application of law and the assessment of the facts of the case. This study aims to examine the concept, legal basis, objectives, requirements, and procedures for filing an appeal in civil cases. The research method employed is normative legal research using statutory and conceptual approaches, conducted through library research on laws and regulations, legal doctrines of scholars, and relevant legal literature. The findings indicate that appeals play an important role in ensuring justice, legal certainty, and the protection of the parties’ rights, while also serving as a control mechanism over decisions of courts of first instance. Accordingly, a proper understanding of appeal as a legal remedy is expected to enhance the effectiveness of civil law enforcement and to realize the principles of fair and balanced justice.Keywords: Legal Remedies, Appeal, Civil Cases, High Court, Civil Procedural Law